Changes in the Prevalence of Coccidian Protozoa in Immunocompromised Patients Over the Last Decade - Özlem ULUSAN BAĞCI; Orçun ZORBOZAN; Kardelen YETİŞMİŞ; Sema AYDOĞDU; Fatma Ömür ARDENİZ; Ayşe Deniz GÖKENGİN; Mehmet KANTAR; Eren SOYALTIN; Önder YAVAŞCAN; Fehmi AKÇİÇEK; Nevin TURGAY (Mediterranean journal of infection, microbes & antimicrobials, 2021)
SummaryIntroduction: Coccidian protozoal infection is one of the most important causes of diarrhea, which could prove to be fatal in immunosuppressed patients. The present study aimed to determine changes in the incidences and prevalence of coccidian protozoa in immunocompromised patients in two different time frames, and thus draw attention toward these neglected microorganisms.Materials and Methods: The present study involved retrospective analysis of 311 stool samples obtained from 311 immunocompromised patients, collected over two time frames (2009 and 2016-2019).Results: The study included 40.5% female and 37.6% pediatric immunocompromised patients (aged 0-18 years). In 2009, the incidences of Cryptosporidium spp. were 51.4% and this decreased to 41.6% in 2016-2019. Cyclospora spp. incidences decreased from 24.6% in 2009 to 9.8% in 2016-2019. Coccidian infection in pediatric patients was found to decrease over the stipulated time, where Cryptosporidium spp. incidences decreased from 63.9% to 34.6% and Cyclospora spp. detection rate decreased from 30.6% to 4.9%. In adults, detection rate for Cryptosporidium spp. changed from 47% to 47.8%, while Cyclospora spp. incidences changed from 22.5% to 14.1%, over the period of 10 years.Conclusion: The study demonstrated no significant changes in coccidian parasitic detection rates in immunocompromised adults over the period of 10 years, which remained high. However, a significant decrease in the detection rates of both Cryptosporidium and Cyclospora spp. was reported in pediatric patients over the years. A comparison with previously reported data revealed higher detection rates of coccidian parasite in immunocompromised patients as compared to the general patient population. These results also highlighted the importance of detailed patient information, especially clinical diagnosis and drug usage, to ensure application of appropriate diagnostic methods for laboratory evaluation of the stool samples obtained from immunocompromised patients. This will further aid in early diagnosis and management of such infections.